Changes of ns‐soot mixing states and shapes in an urban area during CalNex. Issue 9 (13th May 2013) - Adachi, Kouji; Buseck, Peter R.
Abstract : [1] Aerosol particles from megacities influence the regional and global climate as well as the health of their occupants. We used transmission electron microscopes (TEMs) to study aerosol particles collected from the Los Angeles area during the 2010 CalNex campaign. We detected major amounts of ns‐soot, defined as consisting of carbon nanospheres, sulfate, sea salt, and organic aerosol (OA) and lesser amounts of brochosome particles from leaf hoppers. Ns‐soot‐particle shapes, mixing states, and abundances varied significantly with sampling times and days. Within plumes having high CO2 concentrations, much ns‐soot was compacted and contained a relatively large number of carbon nanospheres. Ns‐soot particles from both CalNex samples and Mexico City, the latter collected in 2006, had a wide range of shapes when mixed with other aerosol particles, but neither sets showed spherical ns‐soot nor the core‐shell configuration that is commonly used in optical calculations. Our TEM observations and light‐absorption calculations of modeled particles indicate that, in contrast to ns‐soot particles that are embedded within other materials or have the hypothesized core‐shell configurations, those attached to other aerosol particles hardly enhance their light absorption. We conclude that the ways in which ns‐soot mixes with other particles explain the observations of smaller light amplification by ns‐soot coatings than model calculations during the CalNex campaign and presumably in other areas. Key Points: Ns‐soot particles have a wide range of shapes, mixing states, and abundances Shapes and mixing states of ns‐soot vary within several hours Aerosol particles attached to soot hardly affect its light absorption